Curbing precarious informal employment and bonded labour in the agriculture sector of Nepal: GEFONT's initiative to liberate Kamaiyas - Bishnu Rimal (International Labour Organization (ILO), 2019)
The Kamaiya liberation campaign was one of the robust interventions of the General Federation of Nepalese Trade Unions (GEFONT), which aimed to put a stop to informal and forced (almost slavery in many dimensions) labour practices. The Kamaiya system was one of the most vulnerable bonded labour systems prevailing in Nepal until the last century. As Kamaiyas were in debt-bondage, they are compelled to work for a landlord from generation to generation. As a first step to liberate the bonded Kamaiyas, GEFONT launched in 1996 the Kamaiya Liberation Forum-Nepal (KLFN) and in the same year organized the Federation of Agricultural Workers of Nepal (FAWN) to represent all agricultural workers, including Kamaiyas. In the succeeding years, GEFONT engaged in various initiatives and actions to bring to the government and to the public the plight of the Kamaiyas. Together with national and international non-government organizations and donor agencies, GEFONT also embarked on various projects and activities aimed at improving the welfare of the Kamaiyas and their families. On 17 July 2000, through a Resolution of Commitment in Parliament, the government declared freedom for the Kamaiyas. The government further prohibited every type of bondage and enacted The Kamaiya Labour (Prohibition) Act in 2002. In spite of gaps in the Act and the inherent problems seen during the rehabilitation of Kamaiyas, there have been positive developments as a result of GEFONT's interventions and initiatives: landless Kamaiyas have received land ownership, houses with toilet facilities, and access to drinking water; children attended schools; almost all former Kamaiya workers received at least a minimum wage; children are increasingly withdrawn from child labour; and around a halfdozen freed Kamaiya have been elected/selected in the parliament, the Constituent Assembly. Also, trade unions have begun to unionize former Kamaiyas along with other agricultural labourers in the districts. Unionization was one of the more satisfactory outcomes of the campaign. At the time FAWN was registered as a federation, the membership rate was high - more than 76,000, about half of which comprised ex-Kamaiyas.
Keywords: 330